2009
DOI: 10.1002/jrs.2313
|View full text |Cite
|
Sign up to set email alerts
|

Rapid outdoor non‐destructive detection of organic minerals using a portable Raman spectrometer

Abstract: Raman spectral signatures have been obtained for a series of organic minerals using a compact portable Raman instrument equipped with 785-nm laser excitation. Well-resolved Raman spectra of crystalline salts of carboxylic acids, whewellite and mellite, as well as of the aromatic mineral idrialite were recorded. For comparative purposes, an amorphous fossil resin, baltic amber, was also investigated. The results obtained confirm that portable Raman instruments can be considered as excellent tools for field geol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 30 publications
1
62
0
Order By: Relevance
“…It has been shown that organic material can readily be detected on-site using 785 nm excitation, and it might be necessary for us to make use of this laser line in addition to green excitation in future. [39] In many spectra, we observed intense peaks corresponding to accretions and alteration products such as gypsum and whewellite, both associated with weathering. The identification of these materials as layers covering the original pigments is a first step in understanding the chemical processes at work in the micro-environment of the paintings.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that organic material can readily be detected on-site using 785 nm excitation, and it might be necessary for us to make use of this laser line in addition to green excitation in future. [39] In many spectra, we observed intense peaks corresponding to accretions and alteration products such as gypsum and whewellite, both associated with weathering. The identification of these materials as layers covering the original pigments is a first step in understanding the chemical processes at work in the micro-environment of the paintings.…”
Section: Resultsmentioning
confidence: 99%
“…Two excitation wavelengths were used, namely 532 nm, which is that adopted for the laser used in the ExoMars RLS Raman spectrometer, and 785 nm which was used with good performance of the portable counterparts for identification of inorganic mineral phases as shown for example in Jehlička et al [75] or Vítek et al [76].…”
mentioning
confidence: 99%
“…These instruments that feature excitation sources of the most often used wavelengths (such as 1064, 785 and 532 nm) have previously proved to be quite useful in the fields of geology and astrobiology; the geological applications tested have included analyses of rockforming [18,19] and organic [20] minerals, as well as carbonaceous material from an Ordovician stromatolite [21]. Biomarker detection in Alpine winter conditions [22][23][24] studies involving handheld instrumentation with astrobiological applications for the icy worlds of Europa and Titan.…”
Section: (A) Applications Of Miniaturized Raman Equipmentmentioning
confidence: 99%